Improving Children's Creativity Abilities Through Drawing Activities in Kindergarten - Ernawati Ernawati; Ninik Nurul Aini; Lukmawati Lukmawati; Tri Hastuti (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2022)
This research was conducted to increase children's creativity through drawing activities. The subjects of this study were 15 students of Bina Insan Jember Kindergarten. This research is action research using the Kemmis & McTaggart model with the implementation procedure starting with the stages of planning, implementing, embedding, and reflection activities. Data were collected through teacher activities in drawing and observation of students' actions while participating in learning activities. The results showed that drawing activities could increase students' creativity based on the child's ability to create original and independent works and the child's ability to create unique and different drawings. The data in the second cycle obtained the completeness of students' learning outcomes with an average in the category very well. The increase in learning outcomes can be seen in the interest of all children in drawing activities using pencils, crayons, and watercolors.